Socio-emotional development from complexity in adolescent students of the Calderón Sector in the City of Quito-Ecuador - Andrade-Rivera, Guadalupe (2022)
The present article exposes the socio-emotional development from the complexity in the adolescent students of the Calderón Sector in the City of Quito, for which an exploratory-descriptive investigation was established, with an information collection methodology, which consisted of interviews with the different actors; teachers, students and parents, to a population of 12,500 families, a sample of 2,500 people was taken. The area of study that has been selected is the Calderón sector (rural) considered a vulnerable sector, due to the high poverty rates that are evident. The results clearly show that 23% of young people feel they can freely express their feelings at home, but 68% say they cannot. So this is the basis for giving priority to applying talks in the sector for the knowledge and development of socio-emotional skills, so that they can improve communicative relationships at home, be able to work with empathy and respect, likewise 45% of teachers praise the achievement of youth or children. 42% almost always and 13% sometimes. In this last group of teachers, they explained that it is not possible to praise or recognize the effort of the students, due to the large number of activities that must comply with the subject of planning. It is concluded that it is important to state that HSE lies in the development environments of young people and also in their families, which will allow the competitive performance of the students, educating from coexistence, respecting the emotions of the other, accepting themselves, and that is why it is necessary today to take on this challenge; to improve education by providing teachers with the necessary tools and become a factor that strengthens the development of this area that is so important in the life of every human being.